The Molecular Basis of Spinocerebellar Ataxia Type 7 - Goswami, Rituparna; Bello, Abudu I.; Bean, Joe; Costanzo, Kara M.; Omer, Bwaar; Cornelio-Parra, Dayanne; Odah, Revan; Ahluwalia, Amit; Allan, Shefaa K.; Nguyen, Nghi; Shores, Taylor; Aziz, N. Ahmad; et al. (Frontiers in Neuroscience, 2022)
Spinocerebellar ataxia type 7 (SCA7) is caused by a CAG trinucleotide repeat expansion in the ataxin 7 (ATXN7) gene, which results in a polyglutamine expansion at the N-terminus of ATXN7. Although ATXN7 is expressed universally, the best characterized symptoms of SCA7 are remarkably tissue specific, including blindness and neurodegeneration in the brain and spinal cord. While it is well established that ATXN7 functions as a subunit of the Spt Ada Gcn5 acetyltransferase chromatin modifying complex, the mechanisms underlying SCA7 remain elusive. Here we review the symptoms of SCA7 and examine functions of ATXN7 that may provide further insights into its pathogenesis.